MOTIVASI PEMERINTAH JEPANG DALAM RENCANA PEMBERIAN BEBAS VISA BAGI TURIS ASAL INDONESIA - Jamil, Aditya Al; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explain about the motivation of Japanese policy provides for visa-free tourists from Indonesia. This research uses descriptive research method in which an explanatory analytical research by trying to assess the phenomenon based on existing data. Secondary data obtained from the documentation media which include data from institutions official website, books, magazines, newspapers, newsletters, the Internet, and other sources.The author uses the perspective of neo-liberalism where neo-liberalism assume that the state is trying to maximize its absolute profits through cooperation. The framework of thinking begins with the theory of foreign policy by K.J Holsti where foreign policy is an action or idea designed by policy makers to solve problems or promote a change in the environment, which is in the policy stance or action from other countries. National interests included where national interests is the purpose of the implementation of the foreign policy of a StateThis study found that Japan change their policy orientation to tourist destination country. Japanese government assess that tourism industry is a promising industry in the 21st century. In the beginning, Japanese government issued a visa-free policy for 67 countries include Indonesia. The motivation of Japanese policies provide free visas to Indonesia for targeting 20 million foreign tourists to visit Japan before the 2020 Olympics Tokyo. Implementation of a visa-free policy of Japan towards Indonesia is a precondition to the citizens of Indonesia to have an e-passport, provide multiple-entry visa to Indonesian Citizen and extend the time of the visit from 15 days to 30 daysKeywords: Tourism, Visa, Visa exemption, Olympic 2020 Tokyo, E-Passport, Multiple-entry